FE modelling and experimental investigation on adhesive joints between clay brick and pultruded frp profiles. (30th November 2019) - Sciarretta, Francesca; Russo, Salvatore
Highlights: GFRP profiles can be adhesively connected as strengthening to traditional brickwork. Push-out tests show cohesive failure across different bonded lengths. Expression of maximum load as a function of bonded length. FE modelling clarifies the marginality of brick cracks in the observed failure. The FE crack pattern output is confirmed by Chalos-Beteille failure criterion. Abstract: The experimental-theoretical work explores the possibility of applying pultruded FRP profiles to the structural strengthening of masonry buildings, as embedded or juxtaposed beams, columns, struts/ties or entire frames. The paper reports and discusses the first investigation on epoxy adhesive joints between traditional brick and pultruded FRP flat profile, with different bonded length. The tests are analogous both to the standard triplet tests for shear properties of brick-mortar joints, and to common push-out tests for steel-concrete or timber-concrete composite members. Then, a 2D FE model of the tested samples is applied the experimental stress-slip relationship as well as a frictional interface model, pointing out that the former is more suitable to describe the experimental behaviour. The tests show that the increase in joint's capacity is not regular at increasing bonded length, due to the possible interaction between different failure mechanisms. However, a linear relationship can be found between the maximum load and the bonded length, which is demonstrated both by the experimental data and FE simulations. The possible relationships of the main parameters (i.e. cracking load, ultimate load, corresponding displacements and stiffness) with the bonded length are also explored. The FE model allowed assessing the stress distribution along the bonded length, which follows a nonlinear pattern with unequal maximum values at the ends of the bonded length.